Management of Insect Pests of maize - Kumar, Pradyumn; Sekhar, J. C.; Soujanya, P. Lakshmi; Kaur, Jaswinder (Indian Farming, 2015)
Maize crop is attacked by over 130 inseet pests, which cause varying degree of damage from seedling to maturity stage. Some pests destroy stored products in godowns, bins, storage structures and packages causing huge amount of loss to the stored food and also deteriorate the food quality.